Production of Feminized Seeds of High CBD Cannabis sativa L. by Manipulation of Sex Expression and Its Application to Breeding - Flajšman, Marko; Slapnik, Miha; Murovec, Jana (Frontiers in Plant Science, 2021)
The use of cannabis plants as a source of therapeutic compounds is gaining great importance since restrictions on its growth and use are gradually reduced throughout the world. Intensification of medical cannabis production stimulated breeding activities aimed at developing new, improved cultivars with precisely defined and stable cannabinoid profiles. Breeding medical cannabis rely significantly on manipulation of sex expression, since only genetically female plants are cultivated. Sex is determined by a pair of sex chromosomes (female XX and male XY), but the presence of Y chromosome is not the sole determining factor for the absence of male flowers on genetically female plants. The effects of several exogenous substances, such as silver thiosulfate, gibberellic acid and colloidal silver, on medical cannabis sex expression were therefore analysed in this study. Substances in various concentrations were tested within 20 different treatments on two high CBD breeding lines. Our results showed that spraying whole plants with STS once is more efficient than application of STS on shoot tips, while spraying plants with 0.01 % gibberellic acid and intensive cutting is ineffective in stimulating the production of male flowers. Additionally, spraying whole plants with colloidal silver was also shown to be effective in induction of male flowers on genetically female plants, since it produced up to 379 male flowers per plant. The viability and fertility of the induced male flowers were confirmed by FDA staining of pollen grains, by in vitro and in vivo germination tests of pollen, by counting the number of seeds developed after hybridisation, and by evaluating germination rates of developed seeds. Finally, the established protocol was implemented for crossing selected genetically female plants. The cannabinoid profile of the progeny was compared to the profile of the parental population and an improvement in biochemical profile of the breeding line was confirmed. The progeny had a higher and more uniform tCBD to tTHC ratio (up to 29.6; average 21.33±0.39) compared to the original population (up to 18.8; average 7.83±1.03). This is the first comprehensive scientific report on induction of fertile male flowers on genetically female plants of medical cannabis (Cannabis sativa L.).